Drug-induced liver injury in cancer patients - V. T. Ivashkin; K. L. Raikhelson; L. K. Palgova; M. V. Maevskaya; O. A. Gerasimova; E. A. Kondrashina; N. V. Marchenko; A. Yu. Baranovsky (Онкогематология, 2020)
This review includes information about epidemiological data, development feature, phenotypes, principles of classification, diagnosis, and prognosis for drug-induced liver injury (DILI). Actual clinical recommendations regarding management of the DILI arising in the chemotherapy of cancer discussed. Drugs that can influence on individual pathogenetic mechanisms of growth and symptoms DILI are considered. Clinical studies for the prophylaxis and treatment of DILI associated with anticancer chemotherapy analyzed in detail. The prevention and treatment regimens for DILI in patients receiving chemotherapy and immunotherapy various localizations of cancer given both in research and in practical recommendations.